2009
DOI: 10.1071/wr08135
|View full text |Cite
|
Sign up to set email alerts
|

The impact of fox control on the relative abundance of forest mammals in East Gippsland, Victoria

Abstract: Predation by European red foxes is believed to be the major cause of the extinction and decline of a large number of native medium-sized terrestrial mammals in Australia. We examined the impact of poisoning of foxes on the relative abundance of a group of medium-sized mammals in an experiment conducted in three large forest blocks in south-eastern Australia. The blocks consisted of paired sites, as follows: one site where poison baiting was used to control foxes (treatment site) and one where foxes were not co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 42 publications
3
83
0
Order By: Relevance
“…Even though fox baiting is effective for the conservation of native medium-sized mammal species (Dexter & Murray, 2009;Saunders et al, 2010), we found that fox baiting was only a cost-effective management strategy for malleefowl in some circumstances, depending on the number of years a site had been baited. However, in most situations, malleefowl conservation did not effectively benefit from fox baiting at current levels of investment.…”
Section: Discussionmentioning
confidence: 86%
“…Even though fox baiting is effective for the conservation of native medium-sized mammal species (Dexter & Murray, 2009;Saunders et al, 2010), we found that fox baiting was only a cost-effective management strategy for malleefowl in some circumstances, depending on the number of years a site had been baited. However, in most situations, malleefowl conservation did not effectively benefit from fox baiting at current levels of investment.…”
Section: Discussionmentioning
confidence: 86%
“…It is apparent that even in the goodquality potoroo habitat offered at both study areas the species may be facing serious predation risk due to its use of patches of open ground cover, particularly during foraging. The effective control of introduced predators, especially foxes, in and around potoroo habitat is also likely to assist in the conservation of the species, particularly following disturbances such as fire (Dexter and Murray 2009). …”
Section: Synopsismentioning
confidence: 99%
“…Securing the long-term conservation of this species will depend on an understanding of its population dynamics at multiple locations across its geographic range, which extends from eastern South Australia to southern Queensland, and includes Tasmania (Johnston 2008). The sensitivity of this species to habitat alteration (Claridge and Barry 2000) and fox predation (Dexter and Murray 2009) is well documented and attests to a need for population monitoring. Camera traps now provide the most cost-effective and least intrusive method for doing this (e.g.…”
Section: Introductionmentioning
confidence: 99%